Classroom versus moodle: A descriptive-comparative report from the experience of building an online course - Ruy, Rosimari; Belda, Francisco Rolfsen (Universidade Estadual de Campinas, 2021)
This article presents an experience report that comparatively describes the formatting of the same teacher training course in environmental education in two virtual learning environments, the LMS Google Classroom and Moodle platforms. Faced with the doubt about which would be the most appropriate for the development of the proposed course, we chose to build it in both, trying to verify the limits and potential of each one in order to decide for one of them at the end of the process. Throughout the article, we describe each stage of formatting the course according to our perceptions, illustrating them with prints of the respective screens. We conclude that both platforms meet the objectives of the developed course, but that Moodle is the most appropriate when we consider that we intend to reach an immense demand for course participants, coming up against, however, the need for a server that will host it for free and without limits for enrolled students.